The Relationship of Vitamin C Intake and Nutritional Status with Stress Levels in T2DM Patients during the COVID Pandemic - Qothrunnadaa Fajr Rooiqoh; Didik Gunawan Tamtomo; Risya Cilmiaty (Universitas Aisyah Pringsewu, 2022)
Diabetes mellitus develops when the insulin hormone's secretion or work activity is reduced, resulting in an increase in blood glucose levels. Diabetes mellitus is one of the comorbid disease associated with COVID-19. Coronavirus Disease-19 is causing concern among DM patients since it has the potential to harm their psychological health. People with diabetes may suffer stress, which might affect their glucose management. Increased glucose levels alter food intake, resulting in weight loss. During the COVID-19 pandemic, the study to know the relationship between vitamin C intake and nutritional status with stress levels in T2DM patients. With a total of 105 respondents, the study was done cross-sectional in three health centres: Bantul 1 Health Center, Bambanglipuro Health Center, and Pajangan Health Center. Respondents involved were T2DM patients who were members of the Chronic Disease Management Program. BMI was used to measure nutritional status, while the Semi-Quantitative-Food Frequency Questionnaire (SQ-FFQ) and the Perceived Stress Scale (PSS-10) were used to determine vitamin C intake and stress levels. The Chi-Square test was used to analyze data in SPSS. This study's nutritional status (p: 0.183) and vitamin C intake (p: 0.055) have a Chi-Square value, indicating that p more 0,05. The conclusion there was no relationship between nutritional status and vitamin C intake and stress levels in T2DM patients. Abstrak: Diabetes melitus terjadi apabila ada kenaikan kadar glukosa darah yang diakibatkan dari penurunan sekresi atau aktivitas kerja hormon insulin. Salah satu penyakit yang komorbid terhadap COVID-19 yaitu diabetes melitus. Penderita DM memiliki kekhawatiran terhadap COVID-19 karena akan dapat berakibat pada kesehatan psikososial. Stres yang dialami oleh penyandang DM dapat berdampak pada gangguan pengontrolan glukosa. Adanya peningkatan kadar glukosa akan mengubah asupan makanan dan terjadi penurunan berat badan. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dan asupan vitamin C terhadap tingkat stres pada penderita DMT2 selama pandemi COVID-19. Penelitian crossectional dilakukan di tiga Puskesmas yaitu Puskesmas Bantul 1, Puskesmas Bambanglipuro, dan Puskesmas Pajangan dengan total responden 105 orang. Responden yang terlibat adalah penderit DMT2 anggota Program Manajemen Penyakit Kronis. Status gizi dihitung dengan IMT, asupan vitamin C dapat diketahui dengan Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ) dan tingkat stress dengan kuesioner Perceived Stress Scale (PSS-10). Analisis data menggunakan SPSS dengan uji Chi-Square. Hasil penelitian ini mempunyai nilai Chi-Square (p:0.183) pada status gizi dan asupan vitamin C (p:0.055), sehingga p lebih dari 0,05 . Kesimpulan menunjukkan tidak adanya hubungan status gizi dan asupan vitamin C dengan tingkat stress pada penderita DMT2.